CYBERATTACKS AND DISINFORMATION CAMPAIGNS - Pally, Yudha Akbar (Journal of Social Political Sciences, 2020)
Donald Trump's victory over Hillary Clinton in 2016 US Presidential Election is one of the most shocking political events of this decade. Various controversies and irregularities have been examined and led to alleged Russia’s roles in the election results. Cyberattacks and disinformation campaigns run by Moscow and the weakness of US election security in preventing and mitigating such online intervention further confirm the failure of modern democracy in cyber and social media era. No one can guarantee that Russian cyberattacks and disinformation campaigns will not reoccur in US Presidential Election this year. The US preparedness and capability in dealing with election cyber threats will not only risk the legitimacy of US Presidency but also the sustainability of democracy to survive the today’s information technology and social media advancement.